Autodesk Revit 2024 Architecture - Hamad, Munir (Mercury Learning and Information, 2023)
Covering all of the major techniques, this book uses both metric and imperial units to illustrate the myriad drawing and editing tools for this popular application. Use the companion files to set up drawing exercises and projects and to see all of the book's figures. Revit 2024 Architecture includes over 50 "mini-workshops" that complete small projects from concept through actual plotting. Solving all of these workshops will help to master Revit Architecture from beginning to end, without overlooking any of the basic commands and functions